Preparation of Cadmium Oxide Thin Films by Spray Technique Using Perfume Atomizer and Effect of Solvent Volume on Their Physical Properties - Shanmugavel, G; Balu, A.R; Nagarethinam, V.S (International Journal of Chemistry and Materials Research, 2014)
Cadmium oxide (CdO) thin films were deposited from starting solutions having different values of solvent volume (30 – 60 ml) by employing a simplified spray technique using perfume atomizer. X-ray diffraction studies showed that all the films exhibit cubic structure with preferential orientation along the (1 1 1) plane. The crystallinity increases as the solvent volume increases. Film coated with 60 ml solvent volume has minimum value of strain (3.972 x 10-3) and dislocation density (1.062 x 1015 lines/m2) which confirm the improved crystallinity of that film. The sheet resistance (Rsh) of the film coated with 30 ml solvent volume was found to be minimum (14.69 x 103 ohm/sq.) and there was a sharp increase in Rsh for higher values of solvent volume. The Energy dispersive X-ray analysis confirms that the number of oxygen vacancies governs the electrical resistivity of the CdO films. The films were found to have good optical characteristics which make them suitable for optoelectronic devices.